Attention bias to threat in mothers with emotional disorders predicts increased offspring anxiety symptoms: a joint cross-sectional and longitudinal analysis. Issue 4 (19th May 2018) - Waters, Allison M.; Candy, Elise M.; Candy, Steven G.
ABSTRACT: There is convincing evidence of the transmission of anxiety and depression from parents to children; however, mechanisms by which this vulnerability is passed on are unclear. Cognitive models and a small body of cross-sectional research suggest that parental attention biases (ABs) may be one mechanism involved in transmission. Longitudinal associations of maternal and offspring ABs with offspring symptoms have been scarcely studied. Forty-three mothers–child dyads were included. All children (7–12 years old) were diagnosis-free while 24 mothers had a lifetime emotional disorder (anxiety or depression) (high risk, HR) and 19 mothers had no psychiatric diagnoses (low risk, LR). This study examined cross-sectional and longitudinal associations of maternal and child AB and child anxiety symptomology at initial and 12-month assessments. ABs were assessed using a visual-probe task with emotional faces. There was a significant cross-sectional but not longitudinal association of increased child anxiety symptoms with increased maternal threat AB for HR but not LR dyads. At the cross-sectional level, increases in HR but not LR offspring anxiety symptomology were associated with maternal threat AB. Larger longitudinal studies are required that examine the interplay between parent–child variables and include multiple time-points of assessment and measures of AB.